ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN MENARCHE DINI - Mukhoirotin, Mukhoirotin; Sulayfiyah, Tri Nili (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2020)
Background: The development task of the age, menarche of age commonly occured at the average of under 12 years old to 14 years old. The purpose of the present study was to analized the factors related with the early menarche.Research Methodology: The research design in this study used analytical descriptive with case control approach. The population in this study was 303 respondents, and 68 respondent was selected by simple random sampling (both in early menarche and normal menarche). The independent variable including social economy (income), adult mass media exposure, and lifestyle, the dependent variable was the incidence of early menarche. The data were collected by using questionnaire and the data were analized by using Chi Square statistical test with 5% significant level (? ? 0.05) and logistic regression.Results: The results of this study showed that 76.5% of participant who have unhealthy lifestyle were experienced early menarche, and 67.6% of the participant who exposed of adult mass media were experienced early menarche. Moreover, 85.3% of the participant who have high income of their parent said that they got early menarche. Based on Chi Square test found that there were relationship between lifestyle (p = 0.003), mass media exposure (p = 0.029), high parent income (P = 0.000) and the prevalence of early menarche. The dominant factors associated with early menarche events in adolescents were income (OR = 24.433, 95% CI: 2.148-277.885).Conclusion: Early menarche was associated with the unhealthy lifestyle, adult mass media exposure, and has a high income of their parent. The female adolecent who got early menarche should have an efforts to prevent the impact of early menarche (risk of breast cancer, uterine myoma) by controlling ideal body weight, a low-fat diet, consuming fruits, vegetables and doing exercise.